Europäisches Arbeitsrecht. Richtlinien, Verordnungen, Übereinkommen = European Labour Law. Directives, Regulations, Conventions = Droit européen du travail. Directives, Règlements, Conventions - Neumann , Daniela (Sellier. European Law Publishers, 2003)
"The labour law of the European Community, termed "social policy" in Title XI of the EC Treaty, consists of a variety of directives concerning employment contracts, employment rights on the restructuring and close down of enterprises, equal treatment, industrial safety and collective labour law. In addition, European enactments exist in the areas of conflict of labour laws and international procedural law. Finally, law from the Council of Europe is also relevant in labour law.